Social support, work-family enrichment and life satisfaction among married nurses in health service - Wan Rashid, Wan Edura; Nordin, Mohamad Sahari; Omar, Azura; Ismail, Izhairi (International Association of Computer Science and Information Technology Press (IACSIT), 2011)
Abstract—The objectives of this research are i) to examine the psychometric properties of the constructs of social-support, work-family enrichment and life satisfaction, ii) to validate the hypothesized interrelationships among the constructs of social support, work-family enrichment and life satisfaction among nurses of public hospitals in Malaysia and iii) to examine the likely mediation effect of work-family enrichment on support-satisfaction relationship. Survey questionnaire was administered to 689 married nurses of public hospitals in Malaysia. A full structural modeling testing was used in SEM with AMOS 17 data-fitting program, supported the hypothesized relationship. The results substantiated the psychometric adequacy of the measure and produced a good-fitting life satisfaction model among nurses.